Enterprise Resource Planning : critical success factors for implementation. - Goh, Karen Sher Chin. (2008)
The implementation of enterprise resource planning is critically examined. Using an intensive case study on BP and other case studies including the local ones, a model that identifies critical succcess factors of ERP implementation is created. The model is useful especially to global firms and their subsidiaries.